Analysis of Factors Affecting the Decision to Purchase Online Case Study (Customer Tapa-Bulango) - Nurain Rahmatia Tamrin; Sudarsono; Ely Ibrahim (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The aims of this study are: 1) To determine the factors that influence purchasing decisions online by consumers in Tapa-Bulango; 2) To identify the dominant factors that influence purchasing decisions online by consumers in Tapa-Bulango. The research method used in this research is qualitative with a descriptive approach. The number of informants used in this study was 7 people. The results show that (1) consumers choose to do online shopping because through online media consumers can get clear information about the products they need; (2) Consumers search for information through internet media and also ask friends or family who have bought the same product; (3) After obtaining clear information, the consumer evaluates the product to be purchased by comparing the quality and price of the goods; (4) In making transaction decisions, there are consumers who choose the COD method because they can still check the products purchased. And there are also consumers who follow the alternatives provided by the online store; (5) After making a purchase, there are consumers who actively comment on the products purchased in the online store comments column and there are also consumers who do not provide any comments.